SKEPTISME AUDITOR SEBAGAI MODERASI PENGARUH KOMPETENSI, INDEPENDENSI DAN INTEGRITAS PADA KUALITAS AUDIT KEPATUHAN : AUDITOR SKEPTISM AS A MODERATION OF THE INFLUENCE OF COMPETENCY, INDEPENDENCE AND INTEGRITY ON COMPLIANCE AUDIT QUALITY - Rika, Basse Upi; Andreas, Andreas; Indrawati, Novita (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to examine and analyze the effect of competence, independence and integrity on compliance audit quality moderated by auditor skepticism in the Inspectorate apparatus throughout Riau Province. The population in this study amounted to 297 respondents with a sample of 171 respondents. The research method was carried out by survey using a questionnaire. The data analysis used in this study is the Warp PLS Structural Equation Modeling (SEM).The results of the research hypothesis testing show that competence, independence and integrity have a positive effect on compliance audit quality. There is a significant influence of auditor skepticism in moderating auditor competence, independence and integrity on compliance audit quality. Based on this research, the theoretical implications can provide a stronger consideration of previous research and the theory that has been explained. One of the managerial implications in this study is that it is hoped that the Inspectorate auditors throughout Riau Province in carrying out compliance audits can maintain a code of ethics as auditors so that they always produce quality compliance audits.